LncRNA-miRNA interplay regulate intestinal regeneration in the sea cucumber Apostichopus japonicus - Fang Su; Igor Yu. Dolmatov; Tianming Wang; Hongsheng Yang; Kui Ding; Libin Zhang; Lina Sun (Computational and Structural Biotechnology Journal)
The sea cucumber Apostichopus japonicus, renowned for its remarkable ability to expel and regenerate its internal organs within weeks, serves as a model organism for regeneration research. However, studies on the role of non-coding RNAs, particularly long non-coding RNA (lncRNA), in intestinal regeneration remain limited. In this study, we identified and performed differential expression analysis of lncRNAs in both normal intestines and intestines at 3 days post evisceration (dpe). A total of 2361 lncRNAs were identified, 183 of which were differentially expressed (DE-lncRNAs). The genes targeted by these lncRNAs, either cis- or trans-acting, were involved in oxidative stress, immune response, extracellular matrix remodeling, and energy metabolism during intestinal regeneration. Notably, MSTRG.6200/miR-7847–3p and MSTRG.18440/miR-4220–5p have been confirmed as interacting lncRNA-miRNA pairs. These results suggest that lncRNAs are key regulators of intestinal regeneration in A. japonicus, offering new insights into the underlying mechanisms and potential targets for enhancing regeneration.